2017
DOI: 10.1155/2017/4973573
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Myoepithelial Carcinoma of the Base of Tongue with Possible Lung Metastases

Abstract: Background Epithelial-myoepithelial carcinomas are rare neoplasms usually arising from the salivary glands. There is limited evidence in the literature on their prognosis in the base of the tongue but other cases have resolved without recurrence. Methods The patient underwent biopsies demonstrating the diagnosis of epithelial-myoepithelial carcinoma of the base of tongue and a PET scan showed multiple bilateral rounded pulmonary nodules. Results The patient declined chemotherapy and radiotherapy to maximise hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Specifically, patients with T2, T3, and T4 tumors showed significantly shorter survival than patients with T1 tumors, patients with M1 tumors showed significantly shorter survival than M0 patients, and patients with nodal metastases showed significantly shorter survival than patients who were N0. Chen et al [ 1 ] reported a rare case of a patient with a primary base of tongue epithelial-myoepithelial carcinoma with neck metastases and multiple lung nodules (T4N2cM1). The patient refused treatment other than biopsy and expired at 18 months post-diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, patients with T2, T3, and T4 tumors showed significantly shorter survival than patients with T1 tumors, patients with M1 tumors showed significantly shorter survival than M0 patients, and patients with nodal metastases showed significantly shorter survival than patients who were N0. Chen et al [ 1 ] reported a rare case of a patient with a primary base of tongue epithelial-myoepithelial carcinoma with neck metastases and multiple lung nodules (T4N2cM1). The patient refused treatment other than biopsy and expired at 18 months post-diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial-myoepithelial carcinoma is a relatively uncommon malignant neoplasm. It comprises approximately 1 to 2% of salivary gland neoplasms [ 1 3 ]. The histology of the tumor shows a biphasic pattern with clear myoepithelial cells encasing ducts with an epithelial lining.…”
Section: Introductionmentioning
confidence: 99%
“…RT has been included in treatment plans since WHO inclusion in 1991, and some authors advocate for a refined incorporation of adjuvant RT in the setting of recurrent or high risk EMC[22,23]. Metastatic cases, while uncommon, have a poor prognosis when observed without chemoradiotherapy[24]. Finally, a biological basis may exist for an enhanced response to RT for more aggressive cancers compared to more indolent tumors[25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Pierard et al [ 45 ] described a primary submandibular gland EMC patient with lung metastases who initially treated with cisplatin+fluorouracil (CF) regimen, but due to the progression of metastases in lung, a second-line paclitaxel combined with cyclophosphamide regimen was used and eventually the disease stabilised and the lung symptoms resolved. Otherwise, EMC of the lung from the base of tongue also was reported [ 46 ]. Therefore, the current treatment of choice for patients with early-staged P-EMC is surgical resection, with follow-up treatment based on the presence or absence of high-risk factors.…”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 99%